Discourse acts: pragmasemantics and pragmatypology - Prykhodko, A. M. (Cognition, Communication, Discourse, 2018)
In this article the author suggests and grounds the idea of considering the discourse act as one of the most important constitutive unities of speech. Analysing pragmasemantical specification of discourse acts and comparing it with that of speech acts, he describes the nomenclature of their main types and kinds in the range of "the way of usage", "the mode of usage", "expected preferences for the speaker and/or the hearer", "the techniques of semiotic fixation".